Att inte spänna kärran framför hästen: precisering av Meads ”rollövertagande” (Sociologisk Forskning, 2010)
Not to put the cart before the horse: clarification of Mead’s ”role taking”George Herbert Mead’s “role taking” is subject to many interpretations. Some dominant definitions restrict role taking to reflective people trying to understand each other and taking on each others' roles. Other definitions restrict role taking to the stage of a developed language. Against these two types of definitions I assert that Meads concept is explanatory, not merely descriptive, functionally as well as existentially. It has a value also on elementary levels of human development, where man is socially similar to other primates. Swedish sociologists have contributed fruitfully to straighten the debate. My intention is to clarify it further, and to explicate my own interpretation. Basic role taking is a non-reflective activity going on in any place where living entities influence each other with gestures in similar ways. In human beings it gives rise to conscious discursive reflectivity, and it coincides phylogenetically and ontogenetically with development of language, rather than being created by it. Role taking emanates from breaking automatic responsivity. It introduces distance and reflectivity and results in conscious social behavior, rather than being produced by such. In this way, role taking is a major step in the development of intelligence on earth.